Writing the Ottomans: Turkish history in early modern England - Ingram, Anders (Early modern literature in history, 2015)
Turkish history in early english print -- Conflict, news, and history -- "The present terrour of the world": Knolles's Generall historie of the Turkes -- Trade, diplomacy, and history -- The War of the Holy League 1683-1699 -- Conclusion